Bilateral deficit of strength after reconstruction of the anterior cruciate ligament DOI: 10.5007/1980-0037.2012v14n1p93 - Tiago Figueiredo; Ingrid Dias; Roberto Simão; Érica Queiroz da Silva Bezerra; Ewertton de Souza Bezerra (Universidade Federal de Santa Catarina, 2012)
The aims of this study were verify the differences between the operated limb (OL) and non-operated limb (NOL) and compare the sum of unilateral actions with bilateral results following the test of 10 repetitions maximum (10RM) for the movements of extension and flexion of the knee in patients after reconstruction of anterior cruciate ligament (ACL). Twenty men (37.8±5.7 years; 179.2±4.9 cm; 87.1±7.5 kg) who underwent surgery for ACL reconstruction with autograph in a segment were observed in two different days, in the movements of knee extension and flexion. A student t-test for dependent samples was applied. It was adopted level of statistical significance p < 0.05. The values found for the OL were smaller in relation to the NOL (p < 0.05), as well as the sum of unilateral load was greater than the bilaterally load (p < 0.05) in both movements. In conclusion, there were significant differences for the two movements analyzed and, for comparison between OL and NOL.